Characterization of Micronutrients and Heavy Metal Content in Organic Fertilizer Made From Fly Ash and Organic Waste - Sari Widya Utami; Roy Aries Permana Tarigan; Betti Widianingsih (UNIVERSITY OF LAMPUNG, 2019)
The production of electrical energy from burning of coal produced large amounts of fly ash waste. Fly ash had the potential to be used as soil ameliorant material because it has a very fine size. The purpose of the research was to to develop a new alternative organic fertilizer and to find out the contents of micronutrients and heavy metal on organic fertilizer with fly ash matterials. The research was conducted by composting some organic matterials that consisted of fly ash, poultry manure, peanute litter, dusk of ripsaw and